(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
Gas-insulated equipment using sulphur hexafluoride (SF\(_6\)) as insulation and arc extinguishing media such as Gas Insulated Station (GIS) has been widely used in the field of high voltage power systems. However, the internal insulation defect existed in GIS would inevitably lead to Partial Discharge (PD), and cause the composition of SF\(_6\) to HF, SF\(_4\), SOF\(_2\), SO\(_2\)F\(_2\) and SO\(_2\) and other characteristic component gases. The decomposition phenomenon would greatly reduce the insulation performance of SF\(_6\) insulated equipment, and lead to insulation faults and power failure. Many sensing nonmaterial’s such as carbon nanotube and graphene, metal oxides such as SnO\(_2\) TiO\(_2\), and ZnO were explored as chemical gas sensors to detect SF\(_6\) decomposed species with rapid response, high sensitivity and selectivity, in order to guarantee the operation status of SF\(_6\) insulation equipments. In this paper, we attempt to comprehensively understand the adsorption and sensing property of BNNT to SO\(_2\), SOF\(_2\) and SO\(_2\)F\(_2\) were investigated based on the DFT method to explore its potential as a chemical gas sensor. Our theoretical simulation results show that BNNT could be a promising sensor for sensitive detection which would be beneficial for evaluating the running status of SF\(_6\) high voltage insulated equipments.